Manajemen Inovasi dan Penciptaan Nilai Organisasi - Hendrik A. E. Lao (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The purpose of this research is to find out how the innovation management and organizational value creation in STAKN Kupang, so that they are able to become a high quality and competitive institution. The research method used was a qualitative research method with informants taken were officials at pascasarjana STAKN Kupang, consisting of three people. Research results obtained, namely: 1) Management Innovation can occur if all components play an active role in being able to provide creative ideas that contribute to the advancement of existing education management. And these creative ideas have gone well in the PAK STAKN Kupang postgraduate study program. 2) value creation in the PAK STAKN Kupang postgraduate study program is carried out well by applying Christian character values as added values such as honesty, discipline, sincerity and sincerity.